Analisis Faktor-Faktor yang Mempengaruhi Efektivitas Sistem Informasi Akuntansi Pada Koperasi Simpan Pinjam di Kecamatan Denpasar Selatan - Kadek Apriada; Putu Riska Wulandari; Ida Bagus Ngurah (Jurnal Inovasi Akuntansi (JIA), 2025)
Accounting information systems are able to provide opportunities for business people to increase efficiency and effectiveness in decision making, thereby enabling companies to achieve competitive advantage. This research aims to test and obtain empirical evidence of the influence of education level, task complexity, work experience, age, and personal abilities on the effectiveness of accounting information systems in Savings and Loans Cooperatives in South Denpasar District. The population in this study were all employees of the Savings and Loans Cooperative in South Denpasar District, totaling 365 people. The sample for this research consisted of 122 respondents with a purposive sampling method. The data analysis technique used in this research is multiple linear regression analysis. The research results show that level of education, task complexity, work experience, and age have no effect on the effectiveness of the accounting information system, while personal abilities have a positive effect on the effectiveness of the accounting information system.